A case series of intestinal adenomatous polyposis of unidentified etiology; a late effect of irradiation?. Issue 1 (December 2016) - Rigter, Lisanne; Kallenberg, Frank; Bastiaansen, Barbara; van Os, Theo; van Leeuwen, Floor; van Leerdam, Monique; Dekker, Evelien
Abstract Background In a large number of patients with multiple gastrointestinal adenomatous polyps, no causal germline mutation can be found. Non-genetic factors may contribute to the development of adenomatous polyps in these unexplained polyposis patients. In the development of gastrointestinal cancer, prior exposure to abdominal radiotherapy has been identified as such a factor, as it increases the gastrointestinal cancer risk in cancer survivors. A relationship of radiotherapy with intestinal polyposis, however, has not yet been described. Despite the increased cancer risk, these cancer survivors do not receive gastrointestinal screening recommendations. This case series describes three patients with adenomatous polyposis after abdominal radiotherapy. Case presentation Patient 1 was diagnosed with testicular cancer at the age of 31 and was treated with hemicastration, radiotherapy and chemotherapy. Thirty-nine years later, he was diagnosed with more than 30 colonic adenomas. Additionally, gastroduodenoscopy revealed a well-differentiated adenocarcinoma in the antrum of the stomach. Patient 2 was diagnosed with a nephroblastoma at the age of 10, which was resected and treated with radiotherapy and chemotherapy. At age 36, a rectal adenocarcinoma was diagnosed and treated by radiotherapy and a total mesorectal excision. During 11 years of surveillance endoscopies, 21 colonic adenomas and three duodenal adenomas were detected. Patient 3 was diagnosed with Hodgkin lymphoma at the age of 20 and treated with radiotherapy, followed by chemotherapy for a recurrence 3 years later. At age 62, a subtotal colectomy was performed because of colonic polyposis: 36 adenomas were detected. During screening gastro-duodenoscopy, three duodenal adenomas were detected. In all three patients, germline analysis did not reveal a mutation in theAPC andMYH genes. The gastric and rectal cancer were both microsatellite stable. Conclusion This report describes three patients with adenomatous polyposis, of which two developed a gastrointestinal cancer. The polyposis was not explained by a germline mutation inAPC orMYH and all patients received abdominal radiotherapy. Although an etiologic role has not been established, an association between radiotherapy and intestinal adenomatous polyposis and the subsequent development of cancer seems very likely in our patients.